2023
DOI: 10.1007/s00240-023-01495-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic versus CT assessment of stone-free status after percutaneous nephrolithotomy (PCNL)

F. O. Hartung,
K. J. Müller,
J. Herrmann
et al.

Abstract: This study is aimed to determine whether postoperative low dose computed tomography (LDCT) imaging is necessary after percutaneous nephrolithotomy (PCNL), or the surgeon's intraoperative assessment of residual fragments (RF) is sufficient and avoidance of postoperative imaging with reduction of radiation exposure can be achieved. Data of all 610 patients who underwent PCNL in prone position in our institution from February 2009 to September 2020 was collected. Parameters such as age, gender, BMI, ASA-Classific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, the surgeon's intraoperative assessment of the stone status is often different from the post-operative CT scan imaging results. In a recent series, Hartung et al reported a sensitivity of only 24% (57 out of 237) in the capability of the surgeon to predict which patient has residual fragments, compared to a post-operative CT scan ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the surgeon's intraoperative assessment of the stone status is often different from the post-operative CT scan imaging results. In a recent series, Hartung et al reported a sensitivity of only 24% (57 out of 237) in the capability of the surgeon to predict which patient has residual fragments, compared to a post-operative CT scan ( 4 ).…”
Section: Introductionmentioning
confidence: 99%